IMPLEMENTASI METODE PEMBELAJARAN PROBLEM SOLVING BERBANTUAN MEDIA VISUAL TERHADAP HASIL BELAJAR PKN KELAS XI MADRASAH ALIYAH NURUL KAROMAH - Achmad Barizi; Hefi Rusnita Dewi; M. Sahid (Penerbit STKIP PGRI Bangkalan, 2019)
Student learning achievement in Class, XI MA Nurul Karomah Bangkalan Paterongan is still relatively low. This is caused by the less optimal use of learning methods and the use of instructional media. Also, the students are less active during teaching and learning activities. Teachers need to implement learning methods that can encourage the activeness and involvement of students in teaching and learning activities. The problem solving method is one of the learning methods that can be chosen by the teacher to meet these expectations. The purpose of this study was to determine how the implementation of problem solving learning methods is when assisted by visual media to the learning achievement of class XI MA Nurul Karomah. In this study the research subjects were students of class XI MA Nurul Karoma. The data collection methods used in this study were the questionnaire and observation methods. The collected data were analyzed by quantitative descriptive analysis. From the results of the study, it showed that there was an increase in learning achievement after receiving learning with problem solving learning methods. The average student learning achievement before the implementation of the problem solving learning method through pretest was 56.3, whereas after applying the problem solving learning method through pretest was 73.3. So it can be concluded that by using problem-based learning methods, the learning activities and student learning achievement were improved.